Implementation of a "real world" School-Based Asthma Therapy program targeting urban children with poorly controlled asthma. (3rd October 2018) - Allen, Elizabeth D.; Arcoleo, Kimberly; Rowe, Courtney; Long, William W.
ABSTRACT: Objective : Describe implementation and clinical impact of a "real world" School-Based Asthma Therapy (SBAT) Program serving an urban, largely Medicaid population in a large midwestern city in the United States. Methods : A retrospective, descriptive evaluation of SBAT was conducted. Students were referred by school nurses or providers, enrolled throughout the year, and could reenroll in subsequent years. A total of 286 students participated in the 2015–2016 school year. Kruskal–Wallis nonparametric testing compared Asthma Control Test™ (ACT) scores from enrollment (anytime between 2013 and 2015) to 2015–2016 for 198 students; and pre- and postenrollment asthma-related emergency department (ED), inpatient, and critical care (pediatric intensive care unit or PICU) utilization rates (events/student/year) for 98 students enrolled for a full year. Results : SBAT participation grew from 17 to 131 schools and from 38 to 268 students between 2013–2014 and 2015–2016. Mean ACT scores increased from 16.2 ( SD = 4.89) to 21.37 ( SD = 3.41) (K-W χ 2 = 35.45, p = 0.008). Healthcare utilization rates from 1-year preenrollment to 1-year postenrollment decreased for ED (0.91–0.44; K-W χ 2 = 18.61, p = 0.0002) and Inpatient (0.38–0.10; K-W χ 2 = 7.68, p = 0.02). Reduction in PICU (0.27–0.02) was not statistically significant. Conclusions : SBAT, modeled after programs shown in controlled trials to improve asthma health markers (1–3 ), was successfully implemented in economically challenged, urban schools. Rapid growth and patient reenrollment reflect program acceptance by schools, providers, and caregivers. Improved ACT scores and healthcare utilization supported program efficacy. SBAT could be one solution to improved asthma control in underserved school-aged pediatric patients.